Response of Genotypes to Culture Media for Callus Induction and Regeneration of Plants from Rice Anthers - Sah, Bindeshwar P (Scientific World, 2010)
Response of genotypes to culture media for callus induction and subsequent regeneration from rice anthers were investigated at Biotechnology Unit, Khumaltar, Lalitpur, Nepal. Boots of several rice genotypes viz. Bindeshwari, Hardinath- 1, Prabhat, Khumal-4, Chhomrong local and Chandnath-3 were cold pretreated at 8±1°C for seven days. Anthers from these boots were aseptically cultured on three different medium designated as Medium A: N6 mineral salts and vitamins (2 mg/l each) + myoinositol 100 mg/l + 2,4-D 2.5 mg/l + kinetin 0.5 mg/l + AgNO3 10 mg/l + maltose 50 gm/l; Medium B: N6 mineral salts and MS vitamins + NAA 4 mg/l + Kinetin 2 mg/l + AgNO3 5 mg/l and sucrose 60 gm/l; and Medium C: Medium B without AgNO3. Results revealed that the response of genotype to various media compositions were highly significant for response of anthers for callus induction and embryogenic calli formation. The interaction between genotypes and media were also significant. Among media, the frequency of callus induction (calli/anthers) was higher in medium A (17.65%) followed by medium B (15.74%) and C (11.19%). The frequency of albino plants was observed to be higher than the frequency of green plantlets. The frequency of total regeneration and green plants recovery were high in medium B. Among genotypes tested over all regeneration was high in rice varieties Chandan nath-3 (14.16%) followed by Chhomrong local (9.89%) and Bindeshwari (8.33%). Significant response of genotypes to media compositions indicated that Bindeshwari (25.0%) followed by Chandan nath-3 (19.33%) can induce higher frequency of plantlets from Embryogenic calli obtained from anthers when cultured in medium B. Genotype Prabhat failed to induce any plantlet. This result can be employed for the anther culture work of F1 hybrids in rice. Key words: Embryogenic callus; Silver nitrate (AgNO3); Cold pretreatment; Incubation; Growth environments; Hormones. DOI: 10.3126/sw.v6i6.2632 Scientific World, Vol. 6, No. 6, July 2008 37-43